Molecular Mechanism Underlying the Regulatory Effect of Vine Tea on Metabolic Syndrome by Targeting Redox Balance and Gut Microbiota - Zhou, Xixin; Song, Ying; Zeng, Chaoxi; Zhang, Haowei; Lv, Chenghao; Shi, Meng; Qin, Si (Frontiers in Nutrition, 2022)
Vine tea is a traditional medicinal and edible resource rich in flavonoids, especially for dihydromyricetin (DHM), exhibiting promising health benefits on intervention of metabolic syndrome, but the specific molecular mechanism has not been systematically elucidated. The present paper aims to summarize the regulatory effects and biological targets of vine tea or DHM on metabolic syndrome, and analyze the underlying potential molecular mechanisms in cells, animals and humans, which mainly by regulating the redox associated signaling pathways including Nrf2/Keap1/ARE, NF-κB/JNK/iNOS, PI3K/IRS2/AKT pathways and the crosstalks between them, and by targeting several key biomarkers. Moreover, vine tea extract or DHM has positive impact on the modulation of intestinal microecology by up-regulating the ratio of Firmicutes/Bacteroidetes and increasing the relative abundance of Akkermansia muciniphila. Therefore, this review updated the latest important theoretical basis and molecular evidence for the development and application of vine tea in dietary functional products or drugs against metabolic syndrome and also imputed the future perspectives to clarify the deep mechanism among vine tea or DHM, redox associated signaling pathways and gut microbiota.